1981
DOI: 10.1128/jcm.14.3.333-341.1981
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of species-specific protein antigens of Rickettsia typhi and Rickettsia prowazekii for immunodiagnosis and immunoprophylaxis

Abstract: A simple procedure for the selective isolation of the protective species-specific protein antigens (SPAs) of Rickettsia typhi and Rickettsia prowazekii was developed to permit use of the SPAs in the immunodiagnosis and immunoprophylaxis of typhus infections. Although the SPAs were readily extracted from lysozyme- or detergent-treated rickettsiae, as measured by rocket immunoelectrophoresis, other polypeptides were also present, as shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 24 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Antibodies to this protein were mainly species-specific and groupspecific; weaker reactions occurred with 135-kDa antigens of the heterologous groups. The prominence in Coomassie blue-stained gels and the patterns of migration and immunoreactivity suggest that the protective species-specific antigens (SPA) of the typhus rickettsiae described by Dasch et al [6,15] belong to this family of antigens.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Antibodies to this protein were mainly species-specific and groupspecific; weaker reactions occurred with 135-kDa antigens of the heterologous groups. The prominence in Coomassie blue-stained gels and the patterns of migration and immunoreactivity suggest that the protective species-specific antigens (SPA) of the typhus rickettsiae described by Dasch et al [6,15] belong to this family of antigens.…”
Section: Resultsmentioning
confidence: 97%
“…Besides distinctive group antigens, the rickettsiae also have cross-reacting antigens [4]. The rickettsial antigens shown to elicit immunity are proteins with molecular masses between 100 and 200 kDa [5,6]. Monoclonal antibodies against some of these antigens have been used to study the antigenic relationships among the rickettsiae [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The analogous protein in TG rickettsiae has been referred to as SPA. an acronym for which there are several documented meanings (Ching e^ ai, 1990;Carl et ai, 1990a,b;Dasch, 1981). To alleviate confusion in terminology, we have termed this rickettsial outer membrane protein, rOmp B.…”
Section: Discussionmentioning
confidence: 99%
“…Although its functional activity is poorly understood, some physical and immunological characteristics have been studied. It is known as a species-specific and protective antigen (1,3). It also elicits dominant antibody reaction demonstrated by polyclonal antisera which were employed in rocket immunoelectrophoresis (4).…”
mentioning
confidence: 99%
“…About 10 mg of recombinant protein was obtained from a 1-liter culture of E. coli. Previously, it was reported that the SLP is a protective antigen and elicits dominant antibody response which could be exploited for clinical use (1,3). However, as R. typhi is an obligate intracellular parasite, it is very difficult to prepare the natural SLP.…”
mentioning
confidence: 99%